Implementasi Kurikulum Berbasis Eco-Education untuk Menanamkan Perilaku Ramah Lingkungan pada Anak Usia 4-5 Tahun di PAUD Permata Hati Bunda Kecamatan Kota Agung Barat Kabupatèn Tanggamus - Yulita, Hera; Sari, Selly Nurlela; Anggraini, Wardah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
The still limited systematic integration of environmental education into the learning process at the Early Childhood Education (ECE) level has the potential to cause low ecological awareness among children from the early stages of their development, even though early childhood is an important phase in character formation, including the development of environmentally caring attitudes. This study aims to analyze the implementation of an eco-education-based curriculum in fostering environmentally caring behavior among children aged 4–5 years at PAUD Permata Hati Bunda, West Kota Agung Subdistrict, Tanggamus Regency. This study employed a descriptive qualitative approach involving 10 respondents consisting of the principal, teachers, and parents of the students. The results showed that the implementation of eco-education had been integrated into daily lesson planning, routine habituation activities, and teacher role modeling in daily activities at school. Through these various activities, children showed the development of environmentally friendly behavior, such as disposing of waste in its proper place, conserving water use, and caring for plants in the school environment. In addition, a process of transfer of learning to the family environment was found, as indicated by the beginning of the implementation of similar habits by children at home. Thus, the consistent implementation of an eco-education-based curriculum is able to foster environmentally caring character in early childhood and encourage the sustainable formation of environmentally friendly behavior through cooperation between schools and families.